Antithrombotic strategies in patients undergoing percutaneous coronary intervention for acute coronary syndrome - Son V Pham; Phuong-Chi T Pham; Phuong-Mai T Pham; et al (Dove Medical Press, 2010)
Son V Pham1, Phuong-Chi T Pham2, Phuong-Mai T Pham3, Jeffrey M Miller4, Phuong-Thu T Pham5, Phuong-Anh T Pham61Bay Pines VA Medical Center, Department of Cardiology, Bay Pines, FL, USA; 2Department of Medicine, Nephrology Division, UCLA-Olive View Medical Center, 3Department of Medicine, Greater Los Angeles VA Medical Center, 4Department of Medicine, Hematology-Oncology Division, UCLA-Olive View Medical Center, 5Department of Medicine, Nephrology Division, Kidney and Pancreas Transplant Program, David Geffen School of Medicine at UCLA, Los Angeles, CA, USA; 6Mercy General Hospital, Heart and Vascular Institute, Department of Cardiology, Sacramento, CA, USAAbstract: In patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS), both periprocedural acute myocardial infarction and bleeding complications have been shown to be associated with early and late mortality. Current standard antithrombotic therapy after coronary stent implantation consists of lifelong aspirin and clopidogrel for a variable period depending in part on the stent type. Despite its well-established efficacy in reducing cardiac-related death, myocardial infarction, and stroke, dual antiplatelet therapy with aspirin and clopidogrel is not without shortcomings. While clopidogrel may be of little beneficial effect if administered immediately prior to PCI and may even increase major bleeding risk if coronary artery bypass grafting is anticipated, early discontinuation of the drug may result in insufficient antiplatelet coverage with thrombotic complications. Optimal and rapid inhibition of platelet activity to suppress ischemic and thrombotic events while minimizing bleeding complications is an important therapeutic goal in the management of patients undergoing percutaneous coronary intervention. In this article we present an overview of the literature on clinical trials evaluating the different aspects of antithrombotic therapy in patients undergoing PCI and discuss the emerging role of these agents in the contemporary era of early invasive coronary intervention. Clinical trial acronyms and their full names are provided in Table 1.Keywords: acute coronary syndrome, percutaneous coronary intervention, aspirin, clopidogrel, glycoprotein IIb/IIIa inhibitors, bivalirudin